SYNTHESIS OF SILVER NANOPARTICLES USING MORINGA OLEIFERA SEEDS, GLYCYRRHIZA GLABRA STEMS, AND ITS ANTI-METHICILLIN-RESISTANT STAPHYLOCOCCUS AUREUS ACTIVITY - KALUGENDO, ELISA; P, KOUSALYA (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The present study focused on synthesizing silver nanoparticles (AgNO3) using Moringa Oleifera seeds and Glycyrrhiza glabra stems. Methods: The synthesized AgNO3 were used to evaluate the antibacterial efficacy of methicillin-resistant Staphylococcus aureus (MRSA) by agar well diffusion method. AgNO3 were produced from silver nitrate using M. oleifera seeds and G. glabra stems. Results: AgNO3 were characterized using UV-visible spectroscopy at a wavelength of 400–460 nm. AgNO3 from G. glabra stems showed high anti- MRSA activity with 32 mm zone of inhibition, and M. oleifera seed extract showed 30 mm inhibition zone of inhibition against MRSA. Conclusion: The biologically synthesized AgNO3 can be used against MRSA.